Trends in reported occupational injuries due to accidents among native-born Swedes and immigrant workers in Sweden 2003–2020 - Emelie Thern; Alicia Nevriana; Letitia Davis; David H. Wegman; Eskil Wadensjö; Katarina Kjellberg; Theo Bodin; Devy L. Elling (Injury Epidemiology)
Abstract Background Although there is a growing dependence on the immigrant workforce in many countries, recent trend analyses on the work-related health of immigrants are scarce. Thus, this study aims to fill this gap by comparing reported occupational injuries due to accidents (OIA) trends among native-born Swedes with first-generation immigrants arriving from different global regions now working in Sweden from 2003 to 2020. Methods A repeated cross-sectional registered-based study was conducted including the total working population (18 years or older) (approximately 3.5-4 million individuals annually). Information on OIA and migrant status was obtained from nationwide registers. The incidence rate (IR) of an OIA per 1000 workers with 95% confidence intervals (CI) was calculated for region of birth, the reason for immigration, and time since immigration for each year. Joinpoint analyses were employed to detect significant shifts in the trends. Results The IR of OIA among native-born workers demonstrated a relatively stable trend between 2003 and 2020. Immigrant workers had in general a higher IR of OIA compared to native-born workers across the study period. Among immigrant workers, a steeper downward trend in OIA was observed until 2008/2010. After 2010, the trends were relatively stable or slightly increasing, depending on the region of birth, reason for immigration, and time since immigration. The stratified analysis demonstrated varying patterns depending on sociodemographic and occupational factors. Conclusions Immigrant workers in Sweden have a higher incidence of occupational injuries than native Swedes. Despite a general downward trend since 2003, young immigrants from Africa and the Middle East show an upward trend, highlighting a concerning increase for an already vulnerable group and potentially worsening health inequalities.